Research on comprehensive quality training strategies for nursing staff in the rotating nursing department (轮转护理部护理人员综合素质培养策略研究) - ZHENG Xiaoyan (郑晓艳); LI Jiayue (李佳玥); LIU Yan (刘焱); TIAN Runxi (田润溪) (中西医结合护理)
With the development of medical science and the transformation and of medical mode, the requirements of comprehensive quality of nursing staff are becoming higher and higher. This paper aims to explore the problems in the comprehensive quality cultivation of nursing staff in the rotating nursing department, and proposes suggestions for the comprehensive quality cultivation of nursing staff. There are problems in the cultivation of technical comprehensive quality, professional comprehensive quality, and self-improvement comprehensive quality. It is necessary to strengthen relevant training and improve the improvement mechanism. Targeted strategies should be carried out to improve the comprehensive quality level of nursing staff in rotating nursing department and improve the quality of nursing services. (随着医学科学技术的发展和医疗模式的转变, 对护理人员综合素质的要求也不断提高。本研究主要探讨轮转护理部护理人员综合素质培养存在的问题, 提出轮转护理部护理人员综合素质培养的建议。轮转护理部护理人员综合素质培养当中, 存在技术综合素质培养、专业综合素质培养和自我提升综合素质培养等方面的问题, 需要加强相关培训, 完善提升机制, 进而提升轮转护理部护理人员的综合素质水平, 提高轮转护理部护理服务的质量。)